The effect of leaders’ mental toughness and leadership competence on follower recognition - Ahn, Byung Ok; Lee, Min Kyung; Kim, Boyoung (Edelweiss Applied Science and Technology, 2025)
Follower recognition of leaders significantly influences organizational trust, role-model perception, and the intention to recommend leaders. While positive recognition can be shaped by leaders’ behaviors and competencies, their psychological resource, namely mental toughness, may also affect followers’ perceptions and evaluations. The purpose of this study was to empirically examine the effects of leaders’ mental toughness and leadership competence on follower recognition within organizational contexts. Using a large-scale 360-degree feedback dataset, we analyzed responses from approximately 1,500 employees evaluating 197 senior executives in South Korean corporations. The results showed that leadership competence had a significant positive effect on follower recognition. In contrast, mental toughness did not have a direct effect on recognition but exerted a full mediating effect through leadership competence. This suggests that mental toughness is not directly perceived by followers; rather, it becomes visible when translated into leadership behaviors, which subsequently lead to positive recognition. The study contributes theoretically and practically by reframing mental toughness as a core psychological resource operating through leadership competence, rather than a mere personal trait, in shaping leader–follower dynamics.